Neonatal tooth with bilateral cleft lip and palate: A case report with review of literature - Kamble, Amol; Dash, Jayant Kumar; Sahoo, Prasanna Kumar; Jadhav, Ganesh; Velani, Priyam (Indian Journal of Child Health, 2022)
Natal and neonatal teeth are present in the oral cavity at birth and during the first 30 days of life, respectively. Management of such teeth is a treatment challenge. The incidence of such natal and neonatal teeth is reported to be 1 in every 1125-30,000 births, respectively. Cleft lip and palate (CLP) is a common dentofacial congenital anomaly of the oral cavity and may be present unilaterally or bilaterally. The occurrence of association of such teeth with unilateral and bilateral CLP cases is reported to be 2% and 10%, respectively. The presence of natal/neonatal teeth in the cleft area complicates the child’s health only in few cases. There is a paucity of information in the literature regarding the simultaneous occurrence of neonatal teeth in bilateral CLP cases. The present paper reported the management of a neonatal tooth present in association with complete bilateral CLP in a 12-day-old male child with review of literature.